Respuestas
Respuesta dada por:
0
Respuesta:
en la foto está la respuesta
Adjuntos:
![](https://es-static.z-dn.net/files/d7a/74f735a863b61ab2c51c4cfb69671632.jpg)
Respuesta dada por:
1
Respuesta:
x= -3 - √89/2 o -3+√89/2
x= -6,21699 (-3 - √89/2) o 3,21699 (-3+√89/2)
Explicación:
2x^2+6x-40=0
simplificamos
x²+3x-20= 0
x= -3 ±√3² -4x1x (-20) / 2x1
x= -3±√9+80/2
x= -3±√89/2
x= -3 - √89/2 o -3+√89/2
x= -6,21699 (-3 - √89/2) o 3,21699 (-3+√89/2)
espero haber sido de ayuda ☺️
rubi3864:
oye nadamas una pregunta
Preguntas similares
hace 4 años
hace 4 años
hace 6 años
hace 6 años
hace 8 años